Car Windshield Wiper in the Brain: Case Report - Liu, Zhenpeng; Hou, Xianzeng; Fan, Xiaoyong; Hu, Yuanyuan; Liu, Guangcun (The Surgery Journal, 2016)
Background Transorbital intracranial penetrating injury is rare. Damage caused by a huge metallic foreign body is very critical and life-threatening.Method We report an extremely rare case of transorbital intracranial penetrating metal strip (a car windshield wiper), which has not previously been reported in the literature.Results Emergency craniotomy was performed; the object was removed successfully, and the patient's life was saved.Conclusion With the life-threatening penetrating brain injury caused by a huge foreign body, prompt surgical treatment and comprehensive postoperative treatment are important to save patients' lives.
Keywords: penetrating brain injury; transorbital; wiper